Analysis of the effect of design parameters and their interactions on the strength of dental restorations with endodontic posts, using finite element models and statistical analysis. Issue 4 (11th March 2016) - González-Lluch, Carmen; Pérez-González, Antonio
Abstract : Many previous studies, both in vitro and with model simulations, have been conducted in an attempt to reach a full understanding of how the different design parameters of an endodontically restored tooth affect its mechanical strength. However, differences in the experimental set-up or modelling conditions and the limited number of parameters studied in each case prevent us from obtaining clear conclusions about the real significance of each parameter. In this work, a new approach is proposed for this purpose based on the combination of a validated three-dimensional parametric biomechanical model of the restored tooth and statistical analysis using full factorial analysis of variance. A two-step approach with two virtual tests (with, respectively, 128 and 81 finite element models) was used in the present work to study the effect of several design parameters on the strength of a restored incisor, using full factorial designs. Within the limitations of this study, and for cases where the parameters are within the ranges that were tested, the conclusions indicate that the material of the post is the most significant factor as far as its strength is concerned, the use of a low Young's modulus being preferable for this component. Once the post material has been chosen, the geometry of the post is of less importance than the Young's modulus selected for the core or, especially, for the crown.